Popularity and Size-Aware Caching With Cooperative Transmission in Hybrid Microwave/ Millimeter Wave Heterogeneous Networks - Ochia, Okechukwu E.; Fapojuwo, Abraham O. (IEEE transactions on communications, 2021)
In this paper, a file popularity and size-aware (PSA) caching scheme is proposed for a hybrid heterogeneous network (HetNet) comprising a file server, macro base stations (BSs) operating in the microwave frequency bands, and pico BSs operating in the millimeter wave frequency wave bands. Different than the state-of-the-art size-weighted popularity (SWP) and popularity-based caching schemes that assume equal file size, the file PSA caching scheme utilizes knowledge of the file popularity and size distributions to maximize the network average cache hit probability and the network average success probability subject to the available cache capacity. Moreover, the maximization of the network average success probability is shown to be non-convex and dynamic programming and branch and bound algorithms are employed to circumvent its convexity. New expressions for the optimal file caching probabilities that maximize the network average success probability in noise-limited and interference-limited HetNet scenarios are provided which are evaluated using numerical techniques. The results demonstrate that the proposed file PSA caching scheme provides up to 7% gain in the network average success probability compared to the SWP-based scheme. Lastly, the combination of coded caching with cooperative transmission achieves up to 40% gain compared to a non-cooperative transmission scheme without coded caching.